Influence of a [Formula Presented] resonance on [Formula Presented] scattering - Haidenbauer, J.; Krein, G. [UNESP] (American Physical Society (APS), 2003)
The impact of a [Formula Presented] resonance with a width of [Formula Presented] or more on the [Formula Presented] elastic cross section and on the [Formula Presented] phase shift is examined within the [Formula Presented] meson-exchange model of the Jülich group. It is shown that the rather strong enhancement of the cross section caused by the presence of a [Formula Presented] with the above properties is not compatible with the existing empirical information on [Formula Presented] scattering. Only a much narrower [Formula Presented] state could be reconciled with the existing data—or, alternatively, the [Formula Presented] state must lie at an energy much closer to the [Formula Presented] threshold. © 2003 The American Physical Society.